A Sardinian Family with Factor XI Deficiency - Barcellona, Doris; Favuzzi, Giovanni; Vannini, Maria Luigia; Piras, Sebastiana Maria; Ruberto, Maria Filomena; Grandone, Elvira; Marongiu, Francesco (Hämostaseologie, 2019)
Introduction Factor XI (FXI) deficiency is a bleeding disorder which causes a bleeding tendency after trauma or surgery. An inhibitor may be acquired secondary to replacement therapy.Aim To study on genetical and functional grounds a family admitted to our Haemostasis and Thrombosis Centre for an incidental finding of a prolonged activated partial thromboplastin time (aPTT) in three members.Methods aPTT mixing test, dosage of FXI activity and antigen, FXI inhibitor titration, DNA analysis and clot waveform analysis (CWA) were performed.Results Patients II.1, II.3 and II.4 showed a severe FXI deficiency (0.7, 0.7 and 1.8%, respectively) and low antigen level. Since the proposita was already treated with plasma, the dosage of the inhibitor was determined to be 6.4 Bethesda units. They were homozygous for the p.Glu117Stop mutation. The other family members were heterozygous. The velocity and the maximum acceleration of the clot formation were lower than those of the other family members and the normal subjects but higher than those of patients with acquired haemophilia A.Conclusion A mixing test of a prolonged aPTT should be performed because it will be present both in patients with or without the inhibitor. A molecular analysis in severe FXI deficiency is warranted as it may have prognostic significance. CWA may be helpful for better understanding the pathophysiology of this kind of defect.
Keywords: factor XI deficiency; FXI inhibitor; bleeding; clot waveform analysis; aPTT